Integrating the iPad into Language Arts Instruction for Students with Disabilities: Engagement and Perspectives. Issue 4 (December 2013) - Cumming, Therese M.; Rodriguez, Cathi Draper
This preliminary mixed method single subject and qualitative interview study explored the incorporation of iPad tablets into the language arts lessons of four elementary school students with language-based disabilities. Using the iPad increased the student's academic engagement, which was measured by monitoring the number of prompts required to keep the students on task. Teacher and student interviews revealed high levels of satisfaction with using the iPad for language arts instruction. These findings confirmed findings from earlier studies that focused on mobile technology and communication. Limitations of the study and future research suggestions are discussed.